The Dance of Change : The Challenges of Sustaining Momentum in Learning Organizations (A Fifth Discipline Resource) /: The Challenges of Sustaining Momentum in Learning Organizations (A Fifth Discipline Resource). (2011) - Kleiner, Art; Smith, Bryan; Roberts, Charlotte; Roth, Geroge; Senge, Peter M; Ross, Richard
No abstract available